The competitive advantages of Sudanese live sheep exporting in export to international market - Abass, Amal Saeed; Emam, Abda Abdalla; Elmulthum, Nagat (Edelweiss Applied Science and Technology, 2024)
This study examines factors determining the competitive advantage of live sheep exports from Sudan, assuming Gawad et. al. (2014) model advanced from Porter (1990) Diamond model of competitive advantage of nations. The results of the study showed that sheep production during the period of the study for selected countries are fluctuating, especially Australia it had a high decreasing in production.in recent years. For exports quantities of live sheep noticed that Sudan and Somalia increasing stocks export sheep to the global market, in reverse Australia has a reduction in export quantities especially in current years. The multiple regression showed that R^2 is high 95%,94%93%for Sudan, Somalia, Jordan respectively this is agreed with model expectations. Expect Australia the result shows that R^2 was 78%. The export value in all countries show an unexpected negative significant response to production for Sudan and Australia, insignificant for Somalia and Jordan. On other hand, all selected countries show a positive response to the value of World imports, except Somalia. Export values of live sheep in Sudan show significant positive response to export value of Somalia, in reverse Somalia export value show negative response to Australian export value. This means Somalia is the competitor country for Australia and also for Sudan in spite of its weak contribution in world imports. For all countries, export values positively respond to export quantity indicating prosperous opportunity for growth of export from all selected countries.